Investigation of New Chromosomal Abnormalities Associated with Recurrent Abortion - Ataei , Mina; Moslehi , Zohreh; Nasrabad , Rafat Rezapour; Modoodi, Mozhgan; Farahbakhsh, Parisa; Rad, Samira Saee (International Journal of Psychosocial Rehabilitation, 2020)
Introduction and objective: recurrent abortion refers to the occurrence of three or more abortions in a clinically known pregnancy before the 20th week. It will be possible to prevent the birth of a disabled child and abortion, if chromosome structural abnormalities are identified. The present study was conducted with the aim of genetic (karyotype) investigation of women with recurrent abortion at Kamali Hospital in Karaj. Methodology: This cross-sectional study was conducted on 69 couples (138 people) with recurrent abortion, referred to Kamali Hospital in Karaj. 2 ml of heparinized blood was taken for high resolution karyotype. The karyotype stages included blood culture for 72 hours, blood cell harvest, protein binding and digestion of chromosomes, preparing slide, and analysis. Chromosomal abnormalities along with the shape of the chromosomes were reported. Chromosomal analysis of abortion products was also performed when accessing the abortion product. Mutation analysis was performed using Chromas software. Data were analyzed by SPSS software. Results: chromosomal rearrangements were found in 7 cases after cytogenetic analysis, 6 of which were female and one was male. Out of these7 cases, six had structural abnormalities and one had Turner Syndrome Mosaicism. Thus, out of 136 patients, 7 (5.14%) had chromosomal abnormalities, 6 (4.35%) of which had structural abnormalities and one (0.72%) had Turner Syndrome Mosaicism. Conclusion: The results of the present study and previous studies suggest that the genetic investigation of the couples is an integral part of investigation of the spontaneous recurrent abortions.